Knowledge, Attitude and Practices of Hepatitis B among Family Members of Hepatitis B Cases in District Dera Ghazi Khan of Punjab, Pakistan: A Community-Based Study (Journal of Fatima Jinnah Medical University, 2025)
Background: Hepatitis B virus (HBV) is a major global health concern, potentially leading to complications like cirrhosis and liver cancer. This study evaluated knowledge, attitudes, and practices regarding HBV among family members of HBV-positive patients in a rural area.Methods: A descriptive cross-sectional study was conducted from January to August 2021 in Union Council Choti Zareen, District Dera Ghazi Khan, Punjab, Pakistan. The study targeted 200 immediate family members of Hepatitis B-positive cases, excluding those residing outside the study area, non-family caregivers, and critically ill individuals. Data was collected through face-to-face interviews. Categorical variables were presented as percentages, while continuous variables were reported as means and standard deviations. Associations were analyzed using the Chi-square test, with significance set at p ≤ 0.05.Results: Knowledge of HBV was universal (100%), with 190 (95%) acquiring information from health personnel. Regarding transmission modes, 172 (86%) had knowledge, with unsafe injections (73, 36.5%) being the most recognized route. Preventive measures were known by 172 (86%). Preventive practices were limited with only 38 (19%) requesting sterilized instruments and 6 (3%) observing safe sexual practices. Knowledge of HBV transmission and prevention was significantly associated with age (p = 0.02, p = 0.015), gender (p = 0.0395), education (p = 0.00), and LHW visits (p = 0.00, p = 0.03).Conclusion: Strengthening health education and enhancing LHW outreach in rural areas is essential to improve HBV knowledge and preventive practices, reducing morbidity and mortality
Keywords: Hepatitis B; Knowledge; attitudes; Health Practices; Rural Population; Pakistan